1998
DOI: 10.1021/ja972937e
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Nε2H and Nδ1H Resonances at the Active-Center Histidine in Chymotrypsin and Subtilisin Complexed to Peptideboronic Acids without Specific 15N Labeling1

Abstract: A combination of 1H and 15N nuclear magnetic resonance experiments have been carried out to assign the two high-frequency 1H resonances that result from the complexation of subtilisin E and MeoSuc-Ala-Ala-Pro-boroPhe, a potent peptideboronic acid inhibitor of both subtilisins from a variety of sources and chymotrypsin. First, it was demonstrated unequivocally using two auxotrophs of Bacillus subtilis that the proton resonances at 16 and 17 ppm pertain to a histidine residue. Next it was shown by both 1D and 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
(52 reference statements)
2
20
0
Order By: Relevance
“…We confirmed the presence of this H‐bond by discovering and interpreting the anomolously large His C ε1 ‐H 1 H chemical shifts present in α‐lytic protease, subtilisin, and their boronic acid‐inhibited complexes. Similar reports for other serine proteases, including a boronic acid complex of subtilisin E soon followed (Bao et al 1998, 1999; Lin et al 1998). The additional H‐bond suggested to us a novel reaction‐driven imidazole ring flip mechanism that could solve a long‐standing dilemma regarding how such enzymes catalyze both the formation and productive breakdown of the tetrahedral intermediates (Ash et al 2000).…”
Section: Methodssupporting
confidence: 65%
“…We confirmed the presence of this H‐bond by discovering and interpreting the anomolously large His C ε1 ‐H 1 H chemical shifts present in α‐lytic protease, subtilisin, and their boronic acid‐inhibited complexes. Similar reports for other serine proteases, including a boronic acid complex of subtilisin E soon followed (Bao et al 1998, 1999; Lin et al 1998). The additional H‐bond suggested to us a novel reaction‐driven imidazole ring flip mechanism that could solve a long‐standing dilemma regarding how such enzymes catalyze both the formation and productive breakdown of the tetrahedral intermediates (Ash et al 2000).…”
Section: Methodssupporting
confidence: 65%
“…Consonni et al (44) have demonstrated that these assignments were to autolyzed fragments of enzyme. Bao et al (41) have recently reported a chemical shift of 9.20 ppm for the MeOSuc-Ala-Ala-Pro-boroPhe (AAPbF) complex of subtilisin E. To the best of our knowledge, our finding of a C 1 OH proton chemical shift (9.18 ppm) for a resting, active subtilisin has not been elsewhere reported. Here we also report a C 1 OH proton pH-independent chemical shift for the subtilisin BPNЈ͞AAPbF complex of 9.45 ppm, to our knowledge the most downfield yet observed (Table 1).…”
mentioning
confidence: 48%
“…The hydrogen-bonded proton at ϳ18 ppm in unligated ␣-chymotrypsin has been assigned to the N ␦1 proton of the imidazolium ion of histidine 57 that is hydrogen-bonded to aspartate 102 (8,10,22). At 4°C this proton titrated from 18.0 Ϯ 0.1 at low pH to 14.7 Ϯ 0.1 at high pH with a pK a of 6.7 Ϯ 0.1 at 4°C.…”
Section: H Nmr Of the Hydrogen-bonded Protons Of ␣-Chymotrypsin And Omentioning
confidence: 99%